(untitled) (Damascus University Journal of agriculture sciences, 2021)
The research was conducted at the Abu Jarash farm and in the laboratory of weed - Faculty of Agriculture -Damascus University in 2020 for studying the effect of integration applying between each of the glyphosate 360 g / l (Lancer®) herbicide at 1/3 and 1/4 of the recommended usage rate and some plant extracts of the Sorghum bicolor L., Medicago sativa L. and Cynodon dactylon L. on the management of three species of weeds associated with Pepper crop in the field, Chenopodium album, Amaranthus retroflexus L., Tribulus terrestris L. The results showed that S. bicolor extract has given the best significant effect on all the studied traits and for all species of tested weeds compared with the rest of the extracts, and T. terrestris was the most sensitive herb. The integration between the reduced herbicide dose and the extracts has resulted controlling of the studied weed plants, with an efficiency of 100% when using 1/3 and 1/4 of the recommended application rate of glyphosate, which was similar to the treatment of applying the herbicide alone according to the recommended application rate. So that consequences an economical saving to the cost of pesticides and reducing their harmful effects on the environment.